Route maps for implant positioning: a review: surgical templates for implant placement - Draksharapu, Manaswini; Duggineni, Chalapathi Rao; Ravi Kumar, C; Harilal, G (International Journal of Dental Materials, 2021)
Dental implants are becoming a more common treatment choice in recent years, with an increasing number of patients preferring this option. Proper implant positioning is the most significant requirement for a successful implant treatment prognosis. A transfer system is necessary to ensure logical continuity between the diagnosis, prosthetic preparation, and surgical phases. Various techniques have been proposed for the fabrication of surgical guide templates in implant dentistry. This paper aims to review the associated literature and recent advancements in this field based on the design concept.